Coordination of protective relays in the substation - Shoaib Shaikh; Samha Shaikh; Arsalan Muhammad Soomar; Syed Hadi Hussain Shah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
To make an electrical system reliable and cost-effective, its protection coordination is crucial. Protection coordination is a study to determine the trip settings of protective devices. This research proposes protection coordination for Mehran University of Engineering and Technology, Jamshoro, Sindh. This study includes the coordination of relays connected at each department to the main relay connected with the main vacuum circuit breakers (VCB) by using the time characteristic curves (TCC) and time delay setting of relays using ETAP software. This method is used for the trip of a particular circuit breaker at a proper time. Hence, if a fault occurs in any department only that department will be disconnected, and the rest of the departments will remain in a working condition. This study helps to maintain the system’s high reliability.